2005
DOI: 10.1097/01.mlg.0000171016.82850.41
|View full text |Cite
|
Sign up to set email alerts
|

Does the 23‐Valent Pneumococcal Vaccine Protect Cochlear Implant Recipients?

Abstract: With regard to the increased risk for bacterial meningitis, the authors recommend priming CI recipients younger than 8 years of age with pneumococcal conjugate vaccine followed by a PPV-23 booster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…38 H influenzae type b conjugate vaccine (Hib) is highly effective for prevention of invasive disease and colonization with this pathogen 39,40 and, presumably, is effective for prevention of acute otitis media attributable to H influenzae type b. Cochlear implant recipients have anticapsular antibody concentrations to H influenzae type b after immunization that are likely to be protective. 37,41 Hib vaccine does not prevent colonization or infection with non-serotype b strains; most H influenzae strains that cause acute otitis media are nontypeable strains, as were the isolates from most cases of H influenzae meningitis in implant recipients. 17 …”
Section: Use Of Pneumococcal and H Influenzae Type B Vaccines For Prementioning
confidence: 99%
“…38 H influenzae type b conjugate vaccine (Hib) is highly effective for prevention of invasive disease and colonization with this pathogen 39,40 and, presumably, is effective for prevention of acute otitis media attributable to H influenzae type b. Cochlear implant recipients have anticapsular antibody concentrations to H influenzae type b after immunization that are likely to be protective. 37,41 Hib vaccine does not prevent colonization or infection with non-serotype b strains; most H influenzae strains that cause acute otitis media are nontypeable strains, as were the isolates from most cases of H influenzae meningitis in implant recipients. 17 …”
Section: Use Of Pneumococcal and H Influenzae Type B Vaccines For Prementioning
confidence: 99%
“…Studies in subjects without a cochlear implant have shown a gradual decline in specific antibody concentrations after a primary series of PPV23, and guidelines recommend booster immuniza- tion after 3 years in patients younger than 10 years and after 6 years in older patients. 23 However, antibody levels may fall below a protective threshold earlier, thus leaving some cochlear implant recipients unprotected before the booster dose. The immunologic memory for longterm protection against pneumococcal disease in implant recipients requires further research.…”
Section: Commentmentioning
confidence: 99%
“…In a recent study, patients Ͻ7 years did not show adequate protection after PPV-23 vaccination and an alternative protocol (initial vaccination with PCV-7, followed after 4 weeks by PPV-23 booster) has been suggested. 28 Furthermore, the implantee population has shown a higher incidence of infectious diseases as the cause of death, which could possibly be explained by the fact that this susceptibility might cause, or might more frequently be associated with, deafness. 29 This susceptibility should induce greater precautions, in all deaf patients, in pre-, peri-, and postimplantation management.…”
Section: Discussionmentioning
confidence: 99%